CDK2AP1 influences immune infiltrates and serves as a prognostic indicator for hepatocellular carcinoma - Che, Yibin; Wang, Ge; Xia, Qiang (Frontiers in Genetics, 2022)
Background: Hepatocellular carcinoma (HCC) is a tumor with high malignancy and poor 5-year survival rate. Excellent tumor markers are very important for early clinical diagnosis and prognosis evaluation. Previous studies have shown that CDK2AP1 (Cyclin-dependent kinase 2-associated protein 1) is involved in cell-cycle and epigenetic regulation. In the present study, we assess CDK2AP1 expression, prognostic value, immunomodulatory and possible influencing pathways in HCC. Method: The Cancer Genome Atlas (TCGA) database was used to analyse gene expression, clinicopathology and prognosis. The protein level of CDK2AP1 in HCC tissues was detected in the Human Protein Atlas (HPA) database. The immune score in HCC to CDKAP1 expression were analyzed using ESTIMATE. Furthermore, we use Tumor IMmune Estimation Resource (TIMER) database to study CDK2AP1 expression and Immune Infiltration Levels in HCC. Co-expressed genes of CDK2AP1 were predicted and elaborated by LinkedOmics. Results: In normal liver tissues, the expression of CDK2AP1 was significantly lower than tumor tissues, and was correlated with the level of clinical stage and histologic grade in HCC patients. Patients with high expression of CDK2AP1 have a poor prognosis than patients with low CDK2AP1 expression. CDK2AP1 expression level exhibits significantly positive correlations with the number of infiltrating B cells, CD4+ T cells, CD8+ T cells, Macrophages, Neutrophils, and DCs in HCC tissues. KEGG enrichment analysis showed that the related pathways affected by CDK2AP1 mainly include: Fc gamma R-mediated phagocytosis, Th1 and Th2 cell differentiation, Cell cycle, etc. Both in vitro and in vivo experiments confirmed that CDK2AP1 promotes the proliferation and metastasis in hepatocellular carcinoma. Our results highlight the role of CDK2AP1 as an important prognostic indicator and immunotherapy target for HCC patients. Conclusions: We found CDK2AP1 as a new prognostic biomarker for HCC, which could help explain changes in the biological processes and immune environment lead to liver cancer development. Therefore, CDK2AP1 is a potential new target for HCC therapy.